Epigenetics studies of fetal alcohol spectrum disorder: where are we now?. (March 2017) - Lussier, Alexandre A; Weinberg, Joanne; Kobor, Michael S
Adverse in utero events can alter the development and function of numerous physiological systems, giving rise to lasting neurodevelopmental deficits. In particular, data have shown that prenatal alcohol exposure can reprogram neurobiological systems, altering developmental trajectories and resulting in increased vulnerability to adverse neurobiological, behavioral and health outcomes. Increasing evidence suggests that epigenetic mechanisms are potential mediators for the reprogramming of neurobiological systems, as they may provide a link between the genome, environmental conditions and neurodevelopmental outcomes. This review outlines the current state of epigenetic research in fetal alcohol spectrum disorder, highlighting the role of epigenetic mechanisms in the reprogramming of neurobiological systems by alcohol and as potential diagnostic tools for fetal alcohol spectrum disorder. We also present an assessment of the current limitations in studies of prenatal alcohol exposure, and highlight the future steps needed in the field.